Woodlot management and livelihoods in a tropical conservation landscape - Bailey, Karen (Ambio, 2021)
In biodiversity hotspots, there is often tension between human needs and conservation, exacerbated when protected areas prevent access to natural resources. Forest-dependent people may compensate for exclusion by managing unprotected forests or cultivating planted woodlots. Outside Bwindi Impenetrable National Park in Uganda, household wood product needs are high and population growth puts pressure on the environment. We investigated the role of privately and collectively managed woodlots in provisioning wood products and supporting local livelihoods. We found that households relied heavily on woodlots for daily needs and as resources during time of need. We also found that locally relevant social institutions, called stretcher groups, played a role in the management of woodlots, providing shared community resources. Privately and collectively owned woodlots support local livelihoods and wood product needs in the region. Long-term management of forests in Uganda should consider the value of woodlots and the mechanisms required to support them.